A Green Approach to the Synthesis of Well‐structured Prussian Blue Cubes for the Effective Electrocatalytic Reduction of Antiprotozoal Agent Coccidiostat Nicarbazin. Issue 8 (24th March 2018) - Akilarasan, Muthumariappan; Kogularasu, Sakthivel; Chen, Shen‐Ming; Govindasamy, Mani; Chen, Tse‐Wei; Ali, M. Ajmal; Al‐Hemaid, Fahad M. A.; Elshikh, M. S.; Farah, M. Abul
Abstract: For the first time, a robust electrochemical sensor to detect the coccidiostat nicarbazin (NCZ) is developed through the green synthesis of Prussian blue cubes from Volvariella volvacea (paddy straw mushroom) extract. Recently, numerous articles were reported about the issue that the prophylactic drugs were injected excessively as a feed additive for fattening the chickens in short period. It is a significant concern that the level of coccidiostat NCZ exceeds the residue limits in the tissues of the meat; mainly, in chicken and eggs. Therefore, it is crucial to develop a sensitive, reproducible and long‐lasting sensor for the real‐time detection of NCZ. Thus, we have generated an electrochemical sensor through the economic screen‐printed carbon electrode (SPCE) modification method. Eco‐friendly Prussian blue cubes are fabricated on the carbon film of SPCE. As a result, the modified electrode showed exceptional electrocatalytic ability towards NCZ and the reduction peak currents are correlated to the concentrations of NCZ. It retains the more extensive working range between 1.25×10 −7 to 1.53×10 −3  mol L −1, and it possesses a very low limit of detection as well as the appreciable sensitivity. This method is successfully applied to the recognition of NCZ in the samples of chicken meat and eggs. Abstract :